Subchronic feeding, allergenicity, and genotoxicity safety evaluations of single strain bacterial protein. (April 2022) - Jonaitis, Tom; Lewis, Elizabeth A.; Lourens, Nicky; Groot, Angelique; Goodman, Richard E.; Mitchell, Daniel; Karpol, Alon; Tracy, Bryan
Abstract: Microbial proteins are potentially important alternatives to animal protein. A safety assessment was conducted on a Clostridium protein which can serve as a high-quality protein source in human food. A battery of toxicity studies was conducted comprising a 14-day dose-range finding dietary study in rats, 90-day dietary study in rats and in vitro genotoxicity studies. The allergenic potential was investigated by bioinformatics analysis. In the 90-day feeding study, rats were fed diets containing 0, 5.0, 7.5, and 10% Clostridium protein. The Clostridium protein-containing diets were well-tolerated and no adverse effects on the health or growth were observed. Significant reductions in neutrophil counts were observed in all female rats compared to controls, which were slightly outside of reference ranges. These effects were not deemed to be adverse due to the absence of comparable findings in male rats and high physiological variability of measured values within groups. A No-Observed-Adverse-Effect-Level (NOAEL) of at least 10% Clostridium protein, the highest dose tested and corresponding to 5, 558 and 6, 671 mg/kg body weight/day for male and female rats, respectively, was established. No evidence of genotoxicity was observed and the allergenic potential was low. These results support the use of Clostridium protein as a food ingredient. Highlights: Safety assessment of Clostridia-based protein for use in human food. No toxicity observed at the highest inclusion level in rats after 90 days of intake. No genotoxicity or mutagenicity observed in Ames or in vitro micronucleus tests. Allergenicity potential determined to be low. All data support Clostridium-based protein is safe and high quality protein source.